Method for predicting fatigue life of low-carbon durable oversized-particle-size cement stabilized macadam

The test pieces were prepared by vibration compaction forming method and fatigue tests were carried out, failure probability and fit parameters were calculated, and fatigue life prediction equations were established, which solved the problem of difficulty in obtaining the fatigue life of road surface materials in the prior art, and achieved accurate prediction of the fatigue life of cement-stabilized gravel in super-large particle size.

CN119807602APending Publication Date: 2025-04-11THE SEVENTH ENGINEERING CO LTD OF CCCC FIRST HIGHWAY ENGINEERING CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411927856.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to directly obtain the fatigue life of pavement materials through indoor testing, and the current specifications do not involve the fatigue equation of ultra-large particle size cement-stabilized gravel.

Method used

Vibration compaction molding method was used to prepare ultra-large particle size cement-stabilized gravel cylinder tests, and perform split strength and split fatigue tests. The failure probability was calculated through fatigue life data, and fit parameters were obtained using the fatigue life equation, and then equivalent fatigue life and fit coefficient were calculated to establish a fatigue life prediction equation.

Benefits of technology

The fatigue life of ultra-large particle size cement stable gravel is accurately predicted, and the problem of difficulty in obtaining fatigue life directly at the construction site is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119807602A_ABST
    Figure CN119807602A_ABST
Patent Text Reader

Abstract

The invention discloses a method for predicting the fatigue life of low-carbon durable oversized-particle-size cement stabilized macadam, and belongs to the technical field of traffic civil engineering. The method comprises the following steps: forming a test piece and curing the test piece; soaking the test piece in water, and respectively carrying out a splitting strength test and a splitting fatigue test on the soaked test piece to obtain the stress level and fatigue life data of the test piece; calculating a failure probability corresponding to the fatigue life data; calculating equivalent fatigue life; calculating fitting coefficients of the fatigue equation under different failure probabilities; and according to the fitting coefficient, establishing a fatigue life equation of the oversized-particle-size cement stabilized macadam under different failure probabilities so as to predict the fatigue life. By adopting the method, the fatigue life equation of the oversized-particle-size cement stabilized macadam can be obtained, and the fatigue life of the oversized-particle-size cement stabilized macadam can be accurately predicted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of traffic civil engineering, and in particular to a method for predicting fatigue life of low-carbon durable ultra-large particle size cement-stabilized crushed stone. Background Art

[0002] Super-large-size cement-stabilized crushed stone refers to cement-stabilized crushed stone with a nominal maximum particle size greater than 37 mm. Compared with traditional cement-stabilized crushed stone, it has the advantages of good crack resistance, high strength, and low cement dosage. In recent years, it has been increasingly used in the semi-rigid base structure of high-grade asphalt pavements. On the other hand, according to the requirements of the current specification "Highway Asphalt Pavement Design Specification (JTGD50-2017)", the fatigue life of pavement materials is a necessary indicator parameter in the design of asphalt pavements. However, due to the complexity of fatigue tests, the high cost of fatigue instruments and equipment, and the high discreteness of fatigue test data, it is difficult to directly obtain the fatigue life of pavement materials through indoor tests at the construction site. Therefore, it is usually predicted in the form of fatigue equations.

[0003] For ultra-large particle size cement stabilized crushed stone, a new type of low-carbon durable semi-rigid base material, it is of great significance to obtain its fatigue equation and accurately predict its fatigue life. However, this is not covered in the current specifications and existing literature. Summary of the invention

[0004] The purpose of the present invention is to provide a method for predicting the fatigue life of low-carbon durable ultra-large particle size cement stabilized crushed stone, and to predict the fatigue life of ultra-large particle size cement stabilized crushed stone through a fatigue equation.

[0005] To achieve the above object, the present invention provides a method for predicting fatigue life of low-carbon durable ultra-large particle size cement-stabilized crushed stone, the steps comprising:

[0006] S1. According to the maximum dry density and the optimum water content, the ultra-large particle size cement-stabilized crushed stone cylinder specimens are prepared by the vibration compaction molding method, and the ultra-large particle size cement-stabilized crushed stone cylinder specimens are cured;

[0007] S2. Place the cured super-large particle size cement-stabilized crushed stone cylinder specimen in a water tank and immerse it in water. After immersion, perform splitting strength test and splitting fatigue test on the specimen respectively. At least 5 stress levels are selected for the splitting fatigue test, and at least 3 fatigue life data are obtained at each stress level.

[0008] S3. Based on the obtained fatigue life data, the corresponding failure probability is calculated, and the fitting parameters at this time are obtained according to the obtained failure probability using the fatigue life equation;

[0009] S4. Using the fatigue life equation to calculate according to the obtained fitting parameters, the equivalent fatigue life corresponding to each stress level under different failure probabilities is obtained;

[0010] S5. According to the stress level and the equivalent fatigue life obtained, the fatigue equation is used to calculate and obtain the fitting coefficient of the fatigue equation under different failure probabilities;

[0011] S6. According to the obtained fitting coefficient, the fatigue life prediction equation of super-large particle size cement-stabilized crushed stone under different failure probabilities is obtained based on the fatigue equation, thereby realizing the prediction of fatigue life.

[0012] Preferably, in step S1, a vertical vibrating compactor is used to compact and shape an ultra-large particle size cement-stabilized crushed stone cylindrical specimen, with a vibration time of 120 seconds and a vibration frequency of 32 Hz.

[0013] Preferably, in step S2, the cured specimen is placed in a water tank at 18-22° C. and immersed in water for 24 hours.

[0014] Preferably, the specific process of step S3 includes:

[0015] Based on the obtained fatigue life data, the corresponding failure probability is calculated using the formula:

[0016]

[0017] Where i is the i-th fatigue life data, i is a natural number not greater than n, n is the number of fatigue life data, P i is the failure probability corresponding to the i-th fatigue life;

[0018] Let x and y conform to univariate linear regression, and calculate the determination coefficient of fatigue life according to linear regression. When the determination coefficient is greater than 0.90, it is determined that the fatigue life data meets the requirements, and the fatigue life equation is used to calculate the fitting parameters t and m at this time according to the obtained failure probability, otherwise the fatigue test is repeated; at the same time, the fatigue life data under all stress levels are tested until all requirements are met. The fatigue life equation is expressed as:

[0019]

[0020] Wherein, P is the failure probability (%), N is the fatigue life (times) obtained from the fatigue test, t and m are fitting parameters, x represents the characteristic parameter of fatigue life, and y represents the characteristic parameter of failure probability.

[0021] Preferably, in step S5, the fatigue equation is expressed as:

[0022]

[0023] in, is the equivalent fatigue life, s is the stress level, w and v are the fitting coefficients.

[0024] Therefore, the present invention adopts the above-mentioned low-carbon durable ultra-large particle size cement stabilized crushed stone fatigue life prediction method, which has the following beneficial effects:

[0025] (1) The method of the present invention predicts through fatigue equations, solving the problem that it is difficult to obtain the fatigue life of pavement materials directly through indoor tests at construction sites due to the complexity of fatigue tests, the high cost of fatigue instruments and equipment, and the high discreteness of fatigue test data;

[0026] (2) The method of the present invention helps to obtain the fatigue life equation of super-large particle size cement stabilized gravel and accurately predict the fatigue life of super-large particle size cement stabilized gravel.

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The figure is a flow chart of a method according to an embodiment of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] Reference Figure 1 The present invention provides a method for predicting fatigue life of low-carbon durable ultra-large-size cement-stabilized crushed stone, the steps comprising:

[0032] S1. According to the maximum dry density and the optimum moisture content, the ultra-large particle size cement-stabilized crushed stone cylindrical specimens were prepared by vibration compaction molding method. The specimen size was Φ200mm×h200mm, the vibration time was 120 seconds, and the vibration frequency was 32Hz.

[0033] According to the method of the current specification "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009)", the super-large particle size cement-stabilized crushed stone cylinder specimen (hereinafter referred to as the specimen) obtained in step 1 is cured for a curing period of not less than 90 days.

[0034] S2. Place the cured super-large particle size cement stabilized gravel cylinder specimens in a water tank and immerse them in water at a temperature of 18-20°C for 24 hours, with a maximum of 0.5 hours added or subtracted. After immersion, perform splitting strength test and splitting fatigue test on the specimens according to the current specification "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009)". For the splitting fatigue test, the same loading method as the splitting strength test is used, the stress control mode is selected, and the load action frequency is 15Hz. At least 5 stress levels are selected for the splitting fatigue test, and at least 3 fatigue life data are obtained at each stress level.

[0035] S3. Sort the fatigue life data obtained from the test under a certain stress level from large to small, calculate the corresponding failure probability, and use the fatigue life equation to obtain the fitting parameters at this time according to the obtained failure probability.

[0036] Specifically, based on the fatigue life data sorted from large to small under a certain stress level, the corresponding failure probability is calculated using formula (1), which is expressed as:

[0037]

[0038] Where i is the i-th fatigue life data (i is a natural number not greater than n), n is the number of fatigue life data, P i is the failure probability corresponding to the i-th fatigue life;

[0039] Let x and y conform to univariate linear regression, and calculate the determination coefficient of fatigue life according to linear regression. When the determination coefficient is greater than 0.90, it is determined that the fatigue life data meets the requirements, and the fatigue life equation is used to calculate the fitting parameters t and m at this time according to the obtained failure probability, otherwise the fatigue test is repeated; at the same time, the fatigue life data under all stress levels are tested until all requirements are met. The fatigue life equation is expressed as:

[0040]

[0041] Wherein, P is the failure probability (%), N is the fatigue life (times) obtained from the fatigue test, t and m are fitting parameters, x represents the characteristic parameter of fatigue life, and y represents the characteristic parameter of failure probability.

[0042] S4. Use the fatigue life equation to calculate according to the obtained fitting parameters to obtain the equivalent fatigue life corresponding to each stress level under different failure probabilities.

[0043] Specifically, the fitting parameters t and m obtained in step S3 are substituted into formula (2), and the equivalent fatigue life corresponding to each stress level under different failure probabilities is calculated based on the fitting parameters t and m.

[0044] S5. According to the stress level and the equivalent fatigue life obtained, the fatigue equation is used to calculate and obtain the fitting coefficient of the fatigue equation under different failure probabilities. The fatigue equation is expressed as:

[0045]

[0046] in, is the equivalent fatigue life, s is the stress level, w and v are the fitting coefficients.

[0047] S6. According to the obtained fitting coefficient, the fatigue life prediction equation of super-large particle size cement-stabilized crushed stone under different failure probabilities is obtained based on the fatigue equation, thereby realizing the prediction of fatigue life.

[0048] Specifically, the obtained fitting coefficients w and v are substituted into formula (3), and based on formula (3), the fatigue life prediction equation of super-large particle size cement-stabilized crushed stone under different failure probabilities is obtained.

[0049] In order to ensure the practicability of the method of the present invention, Dunshi P.O42.5 cement and limestone aggregate produced in a certain area are taken as examples for illustration, and the specific situation is as follows.

[0050] S1. According to the maximum dry density and optimum water content, a vertical vibrating compactor is used to compact and form a cylindrical specimen of cement-stabilized crushed stone with an ultra-large particle size. The specimen size is Φ200mm×h200mm, the vibration time is 120 seconds, the vibration frequency is 32Hz, the cement dosage in the specimen is 2.5%, and the mineral gradation is shown in Table 1;

[0051] Table 1 Grading of super-large particle size cement-stabilized crushed stone aggregate

[0052]

[0053] According to the method of the current specification "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009)", the specimens obtained in step 1 were cured for 119 days.

[0054] S2. Place the cured specimens in a 20℃ water tank and soak them in water for 24 hours. Perform splitting strength test and splitting fatigue test on the specimens according to the current specification "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009)". The stress levels of the splitting fatigue test are 0.65, 0.7, 0.75, 0.8, and 0.85, and three fatigue life data are obtained at each stress level. The splitting strength is 1.76MPa, and the splitting fatigue test results are shown in Table 2. It can be seen from the calculation that all fatigue data meet the requirements.

[0055] Table 2 Fatigue test results

[0056]

[0057]

[0058] S3. Sort the fatigue life data in Table 2 from large to small, and calculate the corresponding failure probability according to formula (1). Then, substitute the fatigue life data and the corresponding failure probability into formula (2) respectively;

[0059] Let x and y be consistent with univariate linear regression. The calculation results are shown in Table 3. It can be seen that the determination coefficient R 2 They are all greater than 0.90, indicating that the fatigue life data at each stress level meet the requirements.

[0060] Table 3 Fatigue test data inspection

[0061]

[0062] S4. Substitute the fitting parameters t and m obtained in step S3 into formula (3) to calculate the equivalent fatigue life corresponding to each stress level under different failure probabilities. As shown in Table 4.

[0063] Table 4 Equivalent fatigue life under different failure probabilities

[0064]

[0065] S5. Equivalent fatigue life Substituting the stress level s into the fatigue equation shown in formula (3), the fitting coefficients w and v of the fatigue equation under different failure probabilities are calculated, as shown in Table 5.

[0066] Table 5 Fatigue equation regression coefficients

[0067]

[0068] S6. Substitute the fitting coefficients w and v obtained in S5 back into formula (3) to obtain the fatigue life equation of super-large particle size cement stabilized gravel under different failure probabilities, as shown in formula (4), which is the fatigue life prediction equation with a failure probability of 50%. The fatigue life prediction of super-large particle size cement stabilized gravel can be realized through the fatigue life prediction equation.

[0069] lgN=1.5717-21.0970lgs(4)

[0070] Therefore, the present invention adopts the above-mentioned low-carbon durable super-large particle size cement stabilized crushed stone fatigue life prediction method to predict the fatigue life of super-large particle size cement stabilized crushed stone through fatigue equation.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for predicting fatigue life of low-carbon durable ultra-large-size cement-stabilized crushed stone, characterized in that the steps include: S1. According to the maximum dry density and the optimum water content, the ultra-large particle size cement-stabilized crushed stone cylinder specimens are prepared by the vibration compaction molding method, and the ultra-large particle size cement-stabilized crushed stone cylinder specimens are cured; S2. Place the cured super-large particle size cement-stabilized crushed stone cylinder specimen in a water tank and immerse it in water. After immersion, perform splitting strength test and splitting fatigue test on the specimen respectively. At least 5 stress levels are selected for the splitting fatigue test, and at least 3 fatigue life data are obtained at each stress level. S3. Based on the obtained fatigue life data, the corresponding failure probability is calculated, and the fitting parameters at this time are obtained according to the obtained failure probability using the fatigue life equation; S4. Using the fatigue life equation to calculate according to the obtained fitting parameters, the equivalent fatigue life corresponding to each stress level under different failure probabilities is obtained; S5. According to the stress level and the equivalent fatigue life obtained, the fatigue equation is used to calculate and obtain the fitting coefficient of the fatigue equation under different failure probabilities; S6. According to the obtained fitting coefficient, the fatigue life prediction equation of super-large particle size cement-stabilized crushed stone under different failure probabilities is obtained based on the fatigue equation, thereby realizing the prediction of fatigue life.

2. The fatigue life prediction method of low-carbon durable ultra-large particle size cement stabilized crushed stone according to claim 1 is characterized by: In step S1, a vertical vibrating compactor is used to compact and shape an ultra-large particle size cement-stabilized crushed stone cylindrical specimen, with a vibration time of 120 seconds and a vibration frequency of 32 Hz.

3. The fatigue life prediction method of low-carbon durable ultra-large particle size cement stabilized crushed stone according to claim 1 is characterized by: In step S2, the cured specimen is placed in a water tank at 18-22° C. and immersed in water for 24 hours.

4. The fatigue life prediction method of low-carbon durable ultra-large particle size cement stabilized crushed stone according to claim 1 is characterized in that: The specific process of step S3 includes: Based on the obtained fatigue life data, the corresponding failure probability is calculated using the formula: Where i is the i-th fatigue life data, n is the number of fatigue life data, P i is the failure probability corresponding to the i-th fatigue life; Let x and y conform to univariate linear regression, and calculate the determination coefficient of fatigue life according to linear regression. When the determination coefficient is greater than 0.90, it is determined that the fatigue life data meets the requirements, and the fatigue life equation is used to calculate the fitting parameters t and m at this time according to the obtained failure probability, otherwise the fatigue test is repeated; at the same time, the fatigue life data under all stress levels are tested until all requirements are met. The fatigue life equation is expressed as: Wherein, P is the failure probability (%), N is the fatigue life (times) obtained from the fatigue test, t and m are fitting parameters, x represents the characteristic parameter of fatigue life, and y represents the characteristic parameter of failure probability.

5. The fatigue life prediction method of low-carbon durable ultra-large-size cement-stabilized crushed stone according to claim 4 is characterized in that: In step S5, the fatigue equation is expressed as: in, is the equivalent fatigue life, s is the stress level, w and v are the fitting coefficients.

Citation Information

Cited By

  • Cement concrete fatigue index determination method considering tension-compression alternating load

    CN120102345A